Pemetaan Potensi Genangan Banjir Berdasarkan Topographic Wetness Index (TWI) di DAS Barumun Bilah (Mapping on the Potential Flood Inundation Based on Topographic Wetness Index of Barumun Bilah Watershed) - Masitoh Munthe; Nursida Arif; Dyah Respati Suryo Sumunar (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2024)
Barumun Bilah watershed covers large rivers, including the Bilah River and the Barumun River. These two rivers often overflow during the rainy season, causing the areas next to the rivers to be flooded. This research aims to map the distribution of flood-prone areas in the Barumun Bilah Watershed. This study utilized a geographic information system (GIS) to process DEM (Digital Elevation Model) data using the Topographic Wetness Index (TWI) method. The results of the analysis were in the form of a map depicting three classes of potential flooding in the area flowed by the Barumun Bilah Watershed, namely the high class covering an area of 247,524.40 ha, the medium category covering an area of 537,620.82 ha, and the low category covering an area of 513,558.70 ha. Bilah Hulu, Labuhanbatu, North Sumatera province, is the largest area in the high class flood potential category with an area of 24,711 ha. The resulting map provides spatial information that could be used as the basis for producing planning documents such as Regional Spatial Plans (RTRW), designing disaster risk mitigation strategies for the community, and determining flood control policies in sub-districts with a high TWI category